METHODOLOGICAL ASPECTS OF IMPROVING PEDAGOGICAL CULTURE AND COMPETENCE (Scientific journal of the Fergana State University, 2024)
In this article, the need to improve pedagogical culture and competence, its unique methods are analyzed, and its methodological aspects are highlighted.